2022
DOI: 10.1038/s41598-022-15898-w
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 potential drugs, drug targets, and biomarkers: a viral-host interaction network-based analysis

Abstract: COVID-19 is a global pandemic impacting the daily living of millions. As variants of the virus evolve, a complete comprehension of the disease and drug targets becomes a decisive duty. The Omicron variant, for example, has a notably high transmission rate verified in 155 countries. We performed integrative transcriptomic and network analyses to identify drug targets and diagnostic biomarkers and repurpose FDA-approved drugs for SARS-CoV-2. Upon the enrichment of 464 differentially expressed genes, pathways reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 78 publications
(99 reference statements)
0
15
0
Order By: Relevance
“…It was observed that hsa-miR-33a-3p targets A46L and A41L genes respectively thereby modulating the host defense mechanisms ( Hasan et al., 2016 ). Recently, other groups have also utilized a diverse set of algorithms to identify the miRNAs that could target SARS-CoV-2 genomes ( Mosharaf et al., 2022 ; Samy et al., 2022 ; Shirvani et al., 2022 ; Zeng et al., 2022 ). In order to further advance our understanding of host miRNAs targeting SARS-CoV-2 genomes, we compared our data with other studies.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that hsa-miR-33a-3p targets A46L and A41L genes respectively thereby modulating the host defense mechanisms ( Hasan et al., 2016 ). Recently, other groups have also utilized a diverse set of algorithms to identify the miRNAs that could target SARS-CoV-2 genomes ( Mosharaf et al., 2022 ; Samy et al., 2022 ; Shirvani et al., 2022 ; Zeng et al., 2022 ). In order to further advance our understanding of host miRNAs targeting SARS-CoV-2 genomes, we compared our data with other studies.…”
Section: Resultsmentioning
confidence: 99%
“…45 This suggests that the search for potential antiviral drugs should also consider targets with anti-inflammatory pathways. 46 We also meta-analysed the SNP-h 2 (proportion of phenotypic variance explained by genetic factors) of COVID-19 susceptibility and severity. The SNP-h 2 estimates for susceptibility and severity phenotypes on observed scale were found to be 6% and 7%, respectively, as depicted in Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…These genes induce overproduction of pro‐inflammatory cytokines, such as type I interferons that cause immunological dysregulation 45 . This suggests that the search for potential antiviral drugs should also consider targets with anti‐inflammatory pathways 46 …”
Section: Discussionmentioning
confidence: 99%
“…We found that higher expression levels in ERG increased the risk of severe COVID-19 which is described for the first time with this role. It has been described as a potential drug target for treatment of COVID-19, but nothing is reported as a severity biomarker [ 27 ].…”
Section: Discussionmentioning
confidence: 99%